The design of dynamic access control for hierarchical sensor networks with key–lock–pair mechanism. (21st November 2014) - Chen, Xi; Liu, Yun; Chang, Chin–Chen; Lin, Changlu
In recent years, Wireless Sensor Networks (WSNs) have been applied extensively. Since low–power and mobile sensor networks with flat topology demand high efficiency, good scalability and security, a new structural dynamic access control scheme is needed. In this paper, we explore the task of providing access privileges in hierarchical sensor networks with directed graph and partially ordered set tools. In some traditional schemes, there will be a huge overhead of calculations on the large–scale network when the new class of sensors joins or an old one leaves. We present a novel, efficient and dynamic access control scheme that makes it unnecessary to change all the keys for the Central Authority (CA) and requires only a small amount of computation for each sensor. Specifically, we make use of a key–lock–pair mechanism based on Newton's interpolating polynomial for key management. Extensive analysis showed that our proposed scheme is secure under security models and efficient for both the CA and users.